Rare small intestinal volvulus from entrapment in hepato-diaphragmatic adhesions in a 45-year-old lady - Olaoye, Iyiade Olatunde (J Surg Case Rep, 2016)
Small intestinal volvulus is rare in adults and rarely caused by string adhesions between the liver and the diaphragm. Similar adhesions were described in Fitz-Hugh-Curtis syndrome. We report a 45-year-old lady with small intestinal volvulus from entrapment of a loop in string adhesions between the liver and the diaphragm. Her plain radiographs showed a significant shadow of the trapped loop.